Fauna and stratification of male orchid bees (Hymenoptera: Apidae) and their preference for odor baits in a forest fragment - Ferreira,MG (2011)
This is a study of the population fluctuation of euglossine species, as well as their preferences for scent baits (cineole, eugenol, vanillin and methyl salicylate) in two forest strata (canopy and understory) at the Reserva Florestal do Azulão, a forest fragment located in the municipality of Dourados, MS, Brazil (22°12'S, 54°55'W). We collected a total of 529 males from four genera and eight species. Diversity and equitability for both strata (understory: H' = 1.195 and J' = 0.6139; canopy: H' = 1.193 and J' = 0.6131) did not show a significant difference and a high similarity index was found (P = 87.5%). On the other hand, abundance was substantially higher in the canopy (n = 358) than in the understory (n = 171). From the scents used, eugenol attracted a larger number of individuals (n = 225), but cineole and vanillin attracted a higher number of species.